'The accommodation I make is turning a blind eye': faculty support for student mothers in higher education. Issue 1 (2nd January 2018) - Dickson, Martina; Tennant, Lilly
ABSTRACT: The levels of support which faculty provide to students have been linked to a number of positive effects on students such as lower rates of attrition, greater satisfaction with college life, enhanced self-concept, improved academic performance and more likelihood of remaining enrolled in college through stressful life periods. There are surely fewer periods of life that are busier than new motherhood. This paper presents research carried out at a higher education institution in the United Arab Emirates. We look at the ways in which faculty interact with new student mothers and employ interviews to explore ways in which faculty acknowledge and offer academic and pastoral support to the new mothers. Their perceptions of students' coping strategies when they combine motherhood and college studies are reported, and the ways in which faculty navigate college policy which relates to the student mothers. Faculty saw themselves as being extremely supportive and flexible towards new mothers. Whilst undergraduate student motherhood was uncommon in their home countries, it was generally felt that the increased organization, efficiency, time management and resilience witnessed in student mothers were assets to the college community. This study also has wider applicability to faculty support of non-traditional students in other settings.